2019
DOI: 10.1021/acs.iecr.9b01214
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered Cu-ZnO/γ-Al2O3 Bifunctional Catalyst with Ultra-Low Cu Content Boosting Dimethyl Ether Steam Reforming and Inhibiting Side Reactions

Abstract: Dimethyl ether steam reforming (DME SR) is one of attractive technologies to online provide H 2 for fuel cells in vehicles. Herein, we adopt a novel sputtering method to prepare a Cu-ZnO/γ-Al 2 O 3 (CuZn− S) bifunctional catalyst with only 2.9 wt % Cu loading. The interaction between Cu and ZnO suppresses the thermal aggregation of Cu nanoparticles in DME SR. The Cu nanoparticles (methanol steam reforming sites) are highly and homogeneously dispersed and anchored on the external surface of γ-Al 2 O 3 (DME hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Previous studies from literature have suggested that there might be a correlation between the adsorption energy (i.e., stability of the system) and the amount of charge exchanged [34][35][36][37][38]. This is because the amount of charge exchanged affects the electrostatic interactions between the adsorbate and the surface.…”
Section: Bader Charge Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from literature have suggested that there might be a correlation between the adsorption energy (i.e., stability of the system) and the amount of charge exchanged [34][35][36][37][38]. This is because the amount of charge exchanged affects the electrostatic interactions between the adsorbate and the surface.…”
Section: Bader Charge Analysismentioning
confidence: 99%
“…To address these issues, γ-Al2O3 was found as a promising replacement for Al2O3 in the support of Cu-based catalysts. The use of γ-Al2O3 help improve the stability and longevity of the catalyst, leading to better overall performance in methanol synthesis [35][36][37]. Optimizing the performance of Cu/ZnO based catalyst hinges on a thorough understanding of the interaction between Cu and ZnO at the atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting scattering is defined as partial differential scattering cross section in which the number of neutrons scattered 𝑑 2 σ per second into the small solid angle ∆Ω with final energy between E ' and (E ' + dE ' ) (equation 2). The partial differen-tial scattering cross section is directly proportional to the scattering function S(Q,E) [30,36].…”
Section: Phonon Inelastic Neutron Scattering (Ins)mentioning
confidence: 99%